STRATEGI KREATIF KAMPANYE PENGGUNAAN EARPHONE YANG AMAN BAGI KESEHATAN TELINGA - Anny Valentina; Sherly Yunita; Siti Nurannisaa Parama Bekti (Jurnal Bahasa Rupa, 2021)
As time evolves, it is easier to find children, young, and adults using earphones to do various things ranging from work to entertainment purposes. The habit of using earphones with a volume that is too loud or too long added with other daily noise and a person's lifestyle can certainly harm their hearing. Therefore, the risk of hearing loss that can arise due to unsafe use of earphones needs to be informed early on to young people. This is because hearing loss due to noise is irreversible, so prevention is the most effective way to protect hearing from the risks that may occur. The research objective was to describe the creative strategy design for the educational campaign using earphones. The campaign's creative strategy is using qualitative methods, observation, interviews, literature studies, and surveys. The target chosen for this campaign strategy is young people aged 18-22 years as the generation who use earphones in their everyday life most of the time. The result of this research is a creative strategy in designing a visual communication campaign using an educational approach with the concept of "your last song". This concept emphasizes the delivery of information that the habit of listening to songs using earphones needs to pay attention to safety and risk aspects.